2005
DOI: 10.1128/cdli.12.4.560-561.2005
|View full text |Cite
|
Sign up to set email alerts
|

Oxcarbazepine-Induced Immunoglobulin Deficiency

Abstract: We are reporting the first case of oxcarbazepine-induced immunoglobulin deficiency. Although this is known to be a rare adverse reaction to various pharmacologics (1,4,5), including the anticonvulsant carbamazepine (3, 6, 10, 11), it has not been previously described with oxcarbazepine.A 49-year-old white female was referred for further investigation of low serum immunoglobulins found as part of an evaluation for chronic bacterial vaginitis and suspected immune deficiency. Her infectious history was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Eeg-Olofsson et al found low serum IgA in patients with focal, mainly temporal lobe epilepsy and lower levels of IgA (23.9%) were detected in another study consisting of the patients with IS and Lennox-Gastaut syndrome. [17][18][19] Because most of our IS cases were in the structural/metabolic, the etiological condition; hospitalization and nutritional deficiency due to hypoxic-ischemic encephalopathy, prematurity, and metabolic disorders could have resulted in immune disturbances ( Table 1). The previous antiepileptic treatment of our 5 IS cases consisted of phenobarbital (3), carbamazepine (1) and valproic acid (1).…”
Section: Discussionmentioning
confidence: 99%
“…Eeg-Olofsson et al found low serum IgA in patients with focal, mainly temporal lobe epilepsy and lower levels of IgA (23.9%) were detected in another study consisting of the patients with IS and Lennox-Gastaut syndrome. [17][18][19] Because most of our IS cases were in the structural/metabolic, the etiological condition; hospitalization and nutritional deficiency due to hypoxic-ischemic encephalopathy, prematurity, and metabolic disorders could have resulted in immune disturbances ( Table 1). The previous antiepileptic treatment of our 5 IS cases consisted of phenobarbital (3), carbamazepine (1) and valproic acid (1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, valproic acid inhibits histone deacetylation and potentially exerts immunomodulatory and anti-tumor effects [108][109][110]. Oxcarbazepine, a derivative of carbamazepine that also inhibits histone deacetylation [111], affects the immune system, especially the production of immunoglobulin, to improve the efficacy of anti-epilepsy therapy [112]. Clobazam is a derivative of benzodiazepine that is used to treat refractory epilepsy (particularly complex partial seizures with secondary generalized seizures) as a monotherapy or in combination with other drugs.…”
Section: Aed Therapymentioning
confidence: 99%
“…57,58 Other common medications associated with hypogammaglobulinemia include rituximab, azathioprine, sulfasalazine, and several anticonvulsants (carbamazepine, levetiracetam, oxcarbazepine, and phenytoin). 5963…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…57,58 Other common medications associated with hypogammaglobulinemia include rituximab, azathioprine, sulfasalazine, and several anticonvulsants (carbamazepine, levetiracetam, oxcarbazepine, and phenytoin). [59][60][61][62][63] The physical examination of a patient with a suspected CVID requires an in-depth focus on the involved organ systems. The chest examination often may reveal wheezing, rhonchi, or crackles in patients with CVID-associated lung disease.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%